Aktualisasi Nilai-Nilai Pendidikan Islam dalam Merevitalisasi Pemahaman Moderasi pada Lembaga Pendidikan di Indonesia - Nashuddin Nashuddin (Schemata: Jurnal Pascasarjana UIN Mataram, 2020)
True education makes people more respectful of differences and understanding diversity. Schools offer openness, moderation, and peace, not closure, extremism, and violence. But in reality on the ground, schools are actually not sterile from the outbreak of intolerance and the virus of radicalism. A number of studies show at one conclusion - which is almost agreed on - that intolerance in the world of education is increasing. Starting from rejecting leaders of different religions, do not want to respect the flag, the veil obligation, to those who openly support the khilafah. The entry of intolerance is assessed entering from three doors. First, teacher. Teacher understanding often determines how students behave and act. Second, the curriculum which is still dogmatic-doctrinaire does not provide space for dialogue and imagination. Third, extra activities are loaded with certain ideologies. In this context, it is necessary to return to voice moderation in schools. Attitudes that are not extreme right, always negate everything; nor extreme left, accommodating anything from outside; but rather be selective-accommodating. Teaching selective-accommodative attitude to students, has its own challenges. Not to mention the tendency of religious ways that are practical, instant, and do not want to be complicated, on the one hand; plus the penetration of social media - borrowing the language of Tom Nicholas (Death of Expertise, 2017) - there is a democratization of information, everyone is equal in it, on the other hand. Making moderation mainstreaming projects in schools has its challenges. Pendidikan sejatinya membuat manusia lebih menghargai perbedaaan dan memahami keragaman.Sekolah mengarjakan keterbukaan, moderasi, dan kedamaian, bukan ketertutupan, ekstrim, dan kekerasan.Akan tetapi fakta di lapangan, sekolah justru tidak streril dari wabah intoleransi dan virus radikalisme. Sejumlah penelitian menunjukkan pada satu kesimpulan –yang hampir disepakati—bahwa intoleransi dalam dunia pendidikan semakian meningkat. Mulai dari menolak pemimpin beda agama, tidak mau menghormat bendera, pewajiban jilbab, sampai yang terang-terangan mendukung khilafah. Masuknya intoleransi dinilai masuk dari tiga pintu. Pertama, guru. Pemahaman guru sering menentukan cara bersikap dan bertindak siswa. Kedua, kurikulum yang masih dogmatis-doktriner, tidak memberikan ruang untuk berdialetika dan berimajinasi. Ketiga, kegiatan ekstra yang sarat dengan ideologi tertentu. Dalam konteks inilah, perlu kembali menyuarakan moderasi di sekolah. Sikap yang tidak ekstrim kanan, selalu menegasikan semuanya; juga tidak ekstrim kiri, menampung apapun dari luar; melainkan bersikap selektif-akomodatif. Mengajarkan sikap selektif-akomodatif kepada peserta didik, mendapat tantangan tersendiri. Belum lagi adanya kecenderungan cara beragama yang praktis, instan, dan tidak mau ribet, di satu sisi; di tambah penetrasi media sosial –meminjam bahasa Tom Nicholas (Matinya Kepakaran, 2017) – terjadi demokratisasi infomasi, semua orang setara di dalamnya, di sisi lain. Membuat proyek pengarusutamaan moderasi di sekolah mendapat tantangannya tersendiri.